(untitled) (Acta Scientiarum. Health Sciences, 2014)
Urinary incontinence (UI), more prevalent in women and influencing their functional decline, increases with age. Current longitudinal study with two data collection in 2005-2006 and 2011 compares the functional profile of urinary continence and incontinence in elderly women. Sixty-eight women were divided into females with urinary continence (CG; n = 62) and females with urinary incontinence (IG; n = 6). Dependent variables measured were obesity and body adiposity indexes and functional fitness. Data were given in means with standard deviation (±) and analyzed by the independent t-test (p < 0.05). There were six cases of UI. In the first evaluation group differences occurred for waist circumference (CG: 85.3±9.7 cm; IG: 91.2 ± 12.4cm; t=-2.267; p < 0.05) and cardiorespiratory fitness (CG: 517.9 ± 67.3 m; IG: 463.0±85.9 m; t = 2.571; p < 0.05). CG had a better functional profile, excepting flexibility and lower limbs strength, in the second evaluation. Women with UI had higher waist circumference and lower cardiorespiratory fitness. This may be due to the relationship between the variables and greater abdominal compression and functional decline. Results show that future public health strategies should focus on these factors to decrease the risk of people developing UI and to improve physical-functional and psycho-social benefits to elderly women.